Dukungan Sosial Keluarga dalam Penyembuhan Remaja Penyalahgunaan Narkoba Studi di Kelurahan Bakti Jaya, Permata Pamulang - Muhammad Dimas Firmansyah; Moh Amin Tohari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Drug abuse is still often found in the surrounding environment, especially among teenagers who are still at school. In Indonesia, drug abuse or illegal drugs is a use that is not for health but for recreation. Most drug users are among teenagers who are still at school, especially among high school students who can be said to be the time when teenagers are searching for their identity. The effect that drugs have on users will cause discomfort and can be psychologically disturbing for users. The aim of this research is to determine family social support for drug abuse. This research uses a case study method with a qualitative approach. The technique for determining informants uses a purposive technique with five key informants and five supporting informants. The research results show that the causes of drug abuse are caused by the environment, high curiosity and other external factors that encourage informants to abuse drugs. The impacts experienced by drug abuse are divided into two categories, namely physical impacts such as withdrawal, while psychological impacts such as slow work, carelessness and difficulty concentrating. Family social support has four supports, namely: informational, assessment, instrumental and emotional.